2021
DOI: 10.1002/sres.2787
|View full text |Cite
|
Sign up to set email alerts
|

Addressing new challenges in smart urban planning using Information and Communication Technologies

Abstract: Cities today face the challenge of achieving more participatory and inclusive urban planning. Information and Communication Technologies make it possible to have access to information on the preferences and real uses that citizens make of urban public space; activities that are not always those foreseen in the original planning of cities. This knowledge provides a new understanding of urban capabilities and opportunities that enables planning closer to citizens' needs and designing cities more intelligently an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It is important that we continue to research self-tracking to better understand self-tracking practices. Previous research using MMR has demonstrated the importance of engaging with physical activity apps for decision making ( Hirsch et al, 2014 , Cook et al, 2016 , Anagnostopoulos, 2020 , Pérez‐delHoyo et al, 2021 ) as well as the importance of engaging with self-tracking practices on a more individual level, to understand the intimacies experienced with a through such technologies ( Hughes and Mee, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that we continue to research self-tracking to better understand self-tracking practices. Previous research using MMR has demonstrated the importance of engaging with physical activity apps for decision making ( Hirsch et al, 2014 , Cook et al, 2016 , Anagnostopoulos, 2020 , Pérez‐delHoyo et al, 2021 ) as well as the importance of engaging with self-tracking practices on a more individual level, to understand the intimacies experienced with a through such technologies ( Hughes and Mee, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Anagnostopoulos (2020) analysed the rise of run commuting, finding that run commuting trips must be better integrated in cities for run commuter’s safety. Similarly, Pérez‐delHoyo et al (2021) analysed running movement through MMR to address challenges in urban planning, highlighting that runners need to feel protected within a city and argues that data from apps like MMR needs to be used within urban planning. Work has also used MMR data to understand the experiences of ‘doing’ running.…”
Section: Framing Social Tracking and Surveillancementioning
confidence: 99%
“…Indeed, advances in sophisticated information and communication (ICT) technology offer ways in which several problems and challenges associated with irregular migration could be eased. Mobile computing, blockchain technology, smart contracts, machine learning (ML) and artificial intelligence (AI), and for instance big data are just a few examples of how ICT can transform the society (Mora et al, 2021;Pérez-delHoyo et al, 2021;Troisi et al, 2022). What follows is that, considering the promise and potential inherent in ICT, it is mandatory that ICT-based solutions are hypothesized, elaborated on, modelled, and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…A first study group emphasized the technological and innovative side of cities. These studies define as smart the cities that implement technological innovations in their services and infrastructures (Pérez‐delHoyo et al, 2021). Studies relating to the IoT or ICT systems insist in this area.…”
Section: Introductionmentioning
confidence: 99%